2014
DOI: 10.1017/jns.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a beetroot juice with high neobetanin content on the early-phase insulin response in healthy volunteers

Abstract: Produce rich in phytochemicals may alter postprandial glucose and insulin responses by interacting with the pathways that regulate glucose uptake and insulin secretion in humans. The aims of the present study were to assess the phytochemical constituents of red beetroot juice and to measure the postprandial glucose and insulin responses elicited by either 225 ml beetroot juice (BEET), a control beverage matched for macronutrient content (MCON) or a glucose beverage in healthy adults. Beetroot juice was a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 54 publications
(65 reference statements)
4
45
0
Order By: Relevance
“…Beetroot juice (commercially available as Beet It shots, James White, UK) from a single batch was purchased from a local health‐food shop and sodium nitrate was purchased from Sigma‐Aldrich Australia (Sydney, NSW, Australia). Studies using Beet It doses of 70 mL report that each dose contains 400 mg nitrate, 21 mg betanin, 1.02 mg betaxanthin, and 22.6 mg total flavonoids (rutin equivalent) . C, C+B, and C+N rats were fed with C diet for the first 8 weeks and then with C, C + B or C + N diets for the last 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beetroot juice (commercially available as Beet It shots, James White, UK) from a single batch was purchased from a local health‐food shop and sodium nitrate was purchased from Sigma‐Aldrich Australia (Sydney, NSW, Australia). Studies using Beet It doses of 70 mL report that each dose contains 400 mg nitrate, 21 mg betanin, 1.02 mg betaxanthin, and 22.6 mg total flavonoids (rutin equivalent) . C, C+B, and C+N rats were fed with C diet for the first 8 weeks and then with C, C + B or C + N diets for the last 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using Beet It doses of 70 mL report that each dose contains 400 mg nitrate, [38] 21 mg betanin, 1.02 mg betaxanthin, and 22.6 mg total flavonoids (rutin equivalent). [39] C, C+B, and C+N rats were fed with C diet for the first 8 weeks and then with C, C + B or C + N diets for the last 8 weeks. H, H+B, and H+N rats were fed with H diet for the first 8 weeks and then with H, H + B, or H + N diets for the last 8 weeks.…”
Section: Rats and Dietsmentioning
confidence: 99%
“…They observed a 50% reduction in the blood sugar levels of mice fed an atherogenic diet (24 wk) when supplemented with betanidin (9.6 mg) for the last 40 d. This study set off a few other investigations on hypoglycemic effect of betalain‐rich preparations or purified betalains. In one of the studies, high neobetanin containing red beet juice fed human volunteers showed significant reduction in postprandial glycemic response in the first 15 min of intake (Wootton‐Beard and others ). Interestingly, corresponding to the hypoglycemic response, insulin response was also observed suggesting reduced insulin requirement.…”
Section: Dietary Safetymentioning
confidence: 98%
“…However, some of these processing technologies have been proven to be beneficial in enhancing antioxidant activity or biological activity of extracted betalains (Krifa and others ;Kim and others ; Kannan ; Lee and others ; Gokhale and Lele ; Ravichandran and others ; Cruz‐Cansino and others ; Nunes and others 2015; Sravan Kumar and others ) due to enhanced co‐extraction of antioxidants such as flavonoids, and phenols. In addition, beetroot juice concentrates with high contents of neobetanin, a degradation product of betanin formed during processing, have been observed to lower postprandial insulin and glucose response (Wootton‐Beard and others ). On the other hand, some of the common processing techniques used for preparing betalain concentrates such as spray‐drying, freeze‐drying, and air‐drying have led to wide variations in pigment composition and other phytochemical profiles in the end‐product (Nemzer and others ).…”
Section: Dietary Safetymentioning
confidence: 99%
“…Betalain pigments have potential benefits in promoting health and preventing diseases of human being by serving as potent antioxidant and possessing anti-inflammatory and chemo-preventive activities in vitro and in vivo [1,2,3,4,5,6]. Betalains also contribute to the early-phase insulin response [7] and play a role in dye-sensitized solar cells (DSSCs) [8,9,10]. The biosynthesis of betalains has become one of the hot research topics due to its high nutritional properties and bioactivities.…”
Section: Introductionmentioning
confidence: 99%